2008
DOI: 10.1111/j.1472-765x.1996.tb00058.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of amylase by the intestinal bacteria of Japanese coastal animals

Abstract: The amylase-producing ability of intestinal bacteria in one marine crab and seven fish species was determined. Mean total viable counts ranged from 1.3 x lo5 to 1.5 x lo8 cfu g-', and Vibrionaceae were predominant in all specimens. Of 1585 strains examined, 341 (21.5%) produced 2 0 . 0 1 U amylase ml-'. Percentage of producers ( 2 0 . 0 1 U ml-') differed among genera/families. High abilities (20-05 U ml-') were found i n 1*4-3-6% of Enterobacteriaceae, Pseudomonas and Vibrionaceae strains. O n the other hand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Probiotics actively inhibit the colonization of potential pathogens in the digestive tract by antibiosis or by competition for nutrients and space, and alteration of the microbial metabolism. It also improves the nutrition by detoxifying the potentially harmful compounds in feeds, by denaturing the potentially indigestible components in the diet by hydrolytic enzymes including amylases and proteases, by producing vitamins, such as biotin and vitamin B12 (Fuller & Turvy 1971; Parker 1974; Sugita, Takahashi & Deguchi 1992; Smoragiewicz, Bielecka, Babuchowski, Boutard & Dubeau 1993; Sugita, Kawasaki, Kumazawa & Deguchi 1996; Hoshino, Ishizaki, Sakamoto, Kumeta, Yumoto, Matsuyama & Ohgiya 1997), by producing inhibitory compounds (Spanggaard, Huber, Nielsen, Sick, Pipper, Martinussen Slierendrecht & Gram 2001) and by stimulating host immunity (Fuller 1992; Gibson, Saavendra, MacFarlane & MacFarlane 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics actively inhibit the colonization of potential pathogens in the digestive tract by antibiosis or by competition for nutrients and space, and alteration of the microbial metabolism. It also improves the nutrition by detoxifying the potentially harmful compounds in feeds, by denaturing the potentially indigestible components in the diet by hydrolytic enzymes including amylases and proteases, by producing vitamins, such as biotin and vitamin B12 (Fuller & Turvy 1971; Parker 1974; Sugita, Takahashi & Deguchi 1992; Smoragiewicz, Bielecka, Babuchowski, Boutard & Dubeau 1993; Sugita, Kawasaki, Kumazawa & Deguchi 1996; Hoshino, Ishizaki, Sakamoto, Kumeta, Yumoto, Matsuyama & Ohgiya 1997), by producing inhibitory compounds (Spanggaard, Huber, Nielsen, Sick, Pipper, Martinussen Slierendrecht & Gram 2001) and by stimulating host immunity (Fuller 1992; Gibson, Saavendra, MacFarlane & MacFarlane 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Enterobacteriaceae and Vibrionaceae isolated from marine fish, and Clostridium sp. in freshwater fish, produce amylase that enables the host to digest dietary starch (Sugita, Kawasaki & Deguchi, ; Sugita, Kawasaki, Kumazawa & Deguchi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Sugita et al . () indicated that the bacteria in marine crab digestive tract secreted amylase. Amino acids can be used by microorganisms for construction of specific cell proteins or can undergo transformations leading to produce different metabolic substances (Ringø & Birkbeck ).…”
Section: Introductionmentioning
confidence: 99%